Profil Tingkat Kemampuan Berpikir Kritis Siswa pada Materi Pencemaran Lingkungan Kelas VII SMPN 3 Lirik Tahun Ajar 2023/2024 - Leni Safitri; Nurkahiro Hidayati (Concept: Journal of Social Humanities and Education, 2024)
Critical thinking skills are very necessary in life because in the 21st century critical thinking skills are really needed for students, because the 21st century is the era of information and technology. This research aims to determine the level of students' critical thinking abilities in science lessons and how often teachers give questions aimed at making students accustomed to and able to manage their thoughts to be more critical. This research uses research instruments in the form of 12 multiple choice critical thinking questions and 10 essays. In this study there were 6 multiple choice indicators and 5 essay indicators. This research method is quantitative research with a survey approach. Surveys are generally a way of collecting data from a number of units or individuals over a large and broad period of time. Based on the results of data processing and analysis regarding the ability to think critically of class VII students at SMPN 3 Lirik for the 2023/2024 academic year, they are categorized as less critical. Based on the results of research conducted by researchers in class VII at SMPN 3 Lirik, the percentage based on material about environmental pollution is multiple choice 53.7 % in the less critical category and the critical thinking ability essay is 6.09% in the less critical category. Based on the results of data processing and analysis of research data that have been described, it can be concluded that the profile of the level of critical thinking abilities of science students in environmental pollution material for class VII SMPN 3 Lirik for the 2023/2024 academic year is in the less critical category.